'Hotine' Exhibition Award - Skarlatos, Dimitrios (My University, 2026)
'Hotine' Exhibition Award from the Photogrammetry & Surveying Department of University College London, awarded to the most deserving student following an M.Sc. course in Surveying or Photogrammetry, based on exam grades.
Keywords: Sciences